Strategi Komunikasi Yayasan A dalam Rekrutmen Pegawai - Sandi, Kadia; Nugroho, Catur; Lestari, Martha Tri (Universitas Batanghari Jambi, 2024)
This research aims to find out how to formulate communication strategies and evaluations in employee recruitment at Foundation A. A descriptive qualitative approach with a constructivism paradigm. The research sample was job applicants using a purposive sampling method. The research data analysis process was carried out using method triangulation and data source triangulation. Based on the research results, the recruitment process carried out by Foundation A is still carried out normatively. Employer branding and company reputation have an important role in attracting potential job applicants to join Foundation A